Corporate crime and the discursive deletion of responsibility: A case study of the Paddington rail crash. (April 2013) - Machin, David; Mayr, Andrea
There has been little in-depth research on media representations of corporate crime in either media studies or critical discourse analysis (CDA). Taking one small step to address this situation, this paper assesses the unfolding press representations of one instance where corporate negligence and greed led to the death of 31 people – the Paddington rail crash in London in 1999. At first the event is covered as a 'disaster' through its associated language of 'accidents' and 'heroes'. Later, issues of corporate responsibility are raised even in the popular press, but there are a number of obstacles to the language of crime and criminality being used.